You are on page 1of 22

The Binomial Theorem

Introduction
In this lesson, we study two ways to expand (a + b)n, where n is a positive to M10SP-IIId-e-1.
integer. The first, which uses Pascal’s Triangle, is applicable if n is not too big,
and if we want to determine all the terms in the expansion. The second method
gives a general formula for the expansion of (a + b) n for any positive integer n.
This formula is useful especially when n is large because it avoids the process of
going through all the coefficients for lower values of n obtained through
Pascal’s
Triangle. Moreover, if only a specific term is required, it can be computed directly
using a simple formula. Lastly, the theorem can be used to derive and prove some
useful and interesting results about sums of combinations.

2.4.1. Pascal’s Triangle and the Concept of Combination

Consider the following powers of a + b:


(a + b)1 = a + b
(a + b)2 = a2 + 2ab + b2
(a + b)3 = a3 + 3a2b + 3ab2 + b3
(a + b)4 = a4 + 4a3b + 6a2b2 + 4ab3 + b4
(a + b)5 = a5 + 5a4b + 10a3b2 + 10a2b3 + 5ab4 + b5

We list down the coefficients of each expansion in a triangular array as


follows:

n=1: 1 1
n=2: 1 2 1
n=3: 1 3 3 1
n=4: 1 4 6 4 1
n=5: 1 5 10 10 5 1
The preceding triangular array of numbers is part of what is called the
Pascal’s Triangle. Named after the French mathematician Blaise Pascal (1623-
1662), some properties of the Triangle are the following:

(1) Each row begins and ends with 1.

(2) Each row has n + 1 numbers.

(3) The second and second to the last number of each row correspond to the
row number.

(4) There is symmetry of the numbers in each row.

(5) The number of entries in a row is one more than the row number (or one
more than the number of entries in the preceding row).

(6) Every middle number after first row is the sum of the two numbers above
it.

It is the last statement which is useful in constructing the succeeding rows of


the triangle.
Example 2.4.1. Use Pascal’s Triangle to expand the expression (2x — 3y)5.

Solution. We use the coefficients in the fifth row of the Pascal’s Triangle.
(2x — 3y)5 = (2x)5 + 5(2x)4(—3y)+ 10(2x)3(—3y)2
+ 10(2x)2(—3y)3 + 5(2x)(—3y)4
+ (—3y)5
= 32x5 — 240x4y + 720x3y2 — 1080x2y3
+ 810xy4 — 243y5 2
Example 2.4 2. Use Pascal’s Triangle to expand (a + b)8.

Solution. We start with the sixth row (or any row of the Pascal’s Triangle
that we remember).

n=6: 1 6 15 20 15 6 1
n=7: 1 7 21 35 35 21 7 1
n=8: 1 8 28 56 70 56 28 8 1
Therefore, we get
(a + b)8 = a8 + 8a7b + 28a6b2 + 56a5b3
+ 70a4b4 + 56a3b5 + 28a2b6
+ 8ab7 + b8 2
We observe that, for each n, the expansion of (a + b)n starts with
an and the exponent of a in the succeeding terms decreases
by 1, while the exponent of b increases by 1. This
observation will be shown to be true in general.

.
Let us review the concept of combination. Recall that C(n, k) or n counts the
number of ways of choosing k objects from a set of n objects. It is alsoΣkuseful to
know some properties of C(n, k):

(1) C(n, 0) = C(n, n) = 1,

(2) C(n, 1) = C(n, n — 1) = n, and

(3) C(n, k) = C(n, n — k).

These properties can explain some of the observations we made on the num-
bers in the Pascal’s Triangle. Recall also the general formula for the number of
combinations of n objects taken k at a time:
✓ ◆
n n!
C(n, k) = = ,
k k!(n — k)!

where 0! = 1 and, for every positive integer n, n! = 1 · 2 · 3 ·· · n.


✓ ◆ ✓ ◆
5 8
Example 2.4.3. Compute and .
3 5
Solution ◆
.

5 5! 5!
= = = 10
3 (5 — 3)!3! 2!3!


8 8! 10!
= = = 56 2
5 (8 — 5)!5! 3!5!
.5Σ
You may observe that the value of and the fourth coefficient in the fifth
3 .8
row of Pascal’s Triangle are the same. In the same manner, Σ5 is equal to the
sixth coefficient in the expansion of (a + b) (see Example 2.4.2). These observed
8

equalities are not coincidental, and they are, in fact, the essence embodied in the
Binomial Theorem, as you will see in the succeeding sessions.

Seatwork/Homework 2.4.1

1. Use Pascal’s Triangle to expand each expression.


(a) (x — 2y)4 Answer: x4 — 8x3y + 24x2y2 — 32xy3 + 16y4
(b) (2a — b2)3 Answer: 8a3 — 12a2b2 + 6ab4 — b6
(c) (a + b)9
Answer: a9 +9a8b+36a7b2 +84a6b3 +126a5b4 +126a4b5 +84a3b6 +36a2b7 +
9ab8 + b9
2. Compute.
✓ ◆
5
(a) Answer: 10
2
✓ ◆
9
(b) Answer: 36
7
✓12◆
(c) Answer: 66
10 ◆

20
(d) Answer: 15504
5 ◆

n n(n — 1)
3. Prove: = .
2 2
Answer: ◆

n n! n(n — 1)(n — 2)! n(n — 1)
2 = (n — 2)!2!= (n — 2)!2! = 2

2.4.2. The Binomial Theorem

As the power n gets larger, the more laborious it would be to use Pascal’s
Triangle (and impractical to use long multiplication) to expand (a + b)n. For
example, using Pascal’s Triangle, we need to compute row by row up to the
thirtieth row to know the coefficients of (a + b)30. It is, therefore, delightful to
know that it is possible to compute the terms of a binomial expansion of
degree n without going through the expansion of all the powers less than n.
We now explain how the concept of combination is used in the expansion of (a
+ b)n.
(a + b)n = (a + b)(a + b)(a + b) ·· · (a + b)

| { z }
n fa c tors
When the distributive law is applied, the expansion of (a + b)n consists of
terms of the form ambi, where 0 m, i n. This term is obtained by choosing a
for m of the factors and b for the rest of the factors. Hence, m + i = n, or m=n
— i. This means that the number of times the term a b will appear in the
n—i i

expansion of (a + b)n equals the number of ways of choosing (n — i) or i


factors from the n factors, which is exactly C(n, i). Therefore, we have

Xn
(a + b)n = n—ibi.
◆ a
n
i=
0 i

To explain the reasoning above, consider the case n = 3.


(a + b)3 = (a + b)(a + b)(a + b)
= aaa + aab + aba + abb + baa + bab + bba + bbb
= a3 + 3a2b + 3ab2 + b3
That is, each term in the expansion is obtained by choosing either a or b in each
factor. The term a3 is obtained when a is chosen each time, while a 2b is obtained
when a is selected 2 times, or equivalently, b is selected exactly once.
We will give another proof of this result using mathematical induction. But
first, we need to prove a result about combinations.

Pascal’s Identity
If n and k are positive integers with kn,
then ✓ ◆ ◆ ✓ ◆.
n+ n n
= +
1k k k—
1

Proof. The result follows from the combination formul


✓ ◆ ✓ ◆ n! n!
n + n = + n
k
k k—1 k!(n — k)! (k — 1)!(n — k + .
1)!
n!(n — k + 1)+ n!(k)
= k!(n — k + 1)!
n!(n — k + 1 + k)
= k!(n + 1 — k)!
n!(n + 1)
=
k!(n + 1 — k)!
(n + 1)!
=
k!(n + 1 — k)!


n+1
=
k

Pascal’s identity explains the method of constructing Pascal’s Triangle,


in which an entry is obtained by adding the two numbers above it. This
identity is also an essential part of the second proof of the Binomial
Theorem, which we now state.
The Binomial Theorem
For any positive integer n,
Xn ◆n an—
n
(a + b) ibi.
i
= i=0

Proof. We use mathematical induction.

Part 1
✓ ✓ ✓
X a1—ibi ab +1 0
a0b1 = a + b
◆ ◆ ◆
=
1 1
i=0 1 1

i 0 1
Hence, the formula is true for n = 1.

Part 2. Assume that k


X✓ ak—ibi.
(a + b)k
= ◆
k
We want to show
i=
that i
0
Xk+1 ✓ k
(a + b)k+1 = ak+1—ibi.

+1

i
i=0

(a + b)k+1 = (a + b)(a + b)k


X
k ✓
= (a + b) ◆ ak—ibi
k

i= i

0
X
k ✓ k ✓ ◆
X ◆ k—i i 0 k
=a k a b +
i=0 b i
X i
i=
ak— ibi
X
✓ k ✓
k
◆ ak—i+1bi ◆ ak—ibi+1
= k k
i=0 +
i i
i=

0
X
✓ ✓ ✓
✓ ◆ k+1 0 ◆ ak+1—ibi ◆ akb1 + ◆ ak—1b2
k a b k k k
= 0
+ +
i= i 0 1
k

1
✓ ◆ ✓ ◆

k k
k 0 k+1
a1bk +

+ ak—2b3 + ·· · + a b
2 k—1 k
X✓ k+1—i
✓ bi + bk+1

k Xk a
k
= ak+1 + ◆ a
k+1—ibi +
i—
k i=
1 ✓ 1 ✓ ◆
k
k
i= i
i

1
✓ ◆ X ✓ ◆
k + 1 k+1 0 k+1
= a b k i— ak+1—ibi 0 k+1
0 ◆Σ k +1 a b
+ i + +
=1
1
Xk+1 ✓k + 1◆
= ak+1—ibi
i
i=0

The last expression above follows from Pascal’s Identity.


Therefore, by the Principle of Mathematical Induction,
X ✓n◆
(a + b)n = an—ibi
i
n
i=
1

for any positive integer n. 2

2.4.3. Terms of a Binomial Expansion

We now apply the Binomial Theorem in di↵erent examples.


Example 2.4 4. Use the Binomial Theorem to expand (x + y)6.

Solution
.
X

6
(x + y) 6
x6—kyk

=
k= k
6

0
✓ ◆ ✓ ◆ ✓ ◆
6 6 6 4 2
= x6y0 + x5y1 + xy
0✓ ◆ 1✓ ◆ 2 ✓ ◆
6 3 3 6 2 4 6 1 5
+ xy + xy + xy
3 4 5
✓ ◆
6 0 6
+ xy
6

= x6 + 6x5y + 15x4y2 + 20x3y3


+ 15x2y2 + 6xy5 + y6 2
Since the expansion of (a + b) begins with k = 0 and ends with k = n, the
n

expansion has n.+ nΣ1n—1


terms. The first term in the expansion is n0 a.n = Σan, the
second term is a b = nan=1 b , the second to the last term is. n abn—1
1 . Σ
Σn n— =
nabn—1, and the last term is n bn = bn. 1
.n Σ
The kth term of the expansion is an—k+1bk—1. If n is even, there is a

middle term, which is the


k—1
.n+1 Σ .n+1. n 2 +1 Σ term.
Σ th If n is odd, there are two middle
terms, the th and + 1 th terms.
2 2

.n Σ
The general term is often represented by k an—k bk . Notice.nthat,
Σ in any term,
the sum of the exponents of a and b is n . The combination k is the coefficient
of the term involving bk. This allows us to compute any particular term without
needing to expand (a + b)n and without listing all the other terms.
. p 20
Example 2.4.5. Find the fifth term in the expansion of 2x y .
Σ
expansion
(a of Solution. The fifth term in the expansion of a fifth power—
+ b)n, it is corresponds to k = 4.
✓ ◆
20 p . Σ
(2x)20—4 (— y)4 = 65536x16 y2
4845
4
= 317521920x16y2 2
⇣ ⌘6
x
Example 2.4 6. Find the middle term in the expansion of + 3y .
2
Solution. Since there are seven terms in the expansion, the middle term is the
fourth term (k = 3), which is
✓ ◆⇣ ⌘ ✓ 3 Σ
6 x 3 (3y)3 = x 27y3 = 135x y .
3 3
2
20 ◆
.

3 2 8 2
Example 2.4.7. Find the term involving x (with exponent 1) in the expansion

2y ◆8
of x2 — .
x

Solution. The general term in the expansion is


✓ ◆ ✓ ◆
8 . 2 Σ8—k 2y k (—2)kyk
x x = x16—
k — ✓ ◆ 2k xk
8 ·
k
✓ ◆
8
= (—2)kx16—2k—kyk
k
✓ ◆
8
= k (—2)kx16—3kyk.
The term involves x if the exponent of x is 1, which means 16 3k = 1, or
k = 5. Hence, the term is

✓ ◆
8
(—2)5xy5 = —1792xy5. 2
5

Seatwork/Homework 2.4.3

1. Use the Binomial Theorem to expand (2a — b2)5.


Answer:
. Σ5
✓ ◆ ✓ ◆
5 5
2a — b2 = (2a)5 + (2a)4b2
0 1
✓ ◆ . Σ2
✓ ◆ . Σ3
5 5
+ (2a)3 b2 + (2a)2 b2
2 3
✓ ◆ . Σ4
✓ ◆
5 5 . 2 Σ5
+ (2a) b 2
+ b
4 5

= 32a5 — 80a4b2 + 80a3b4 — 40a2b6


+ 10ab8 — b10

✓ ◆11
x 1/3 2 .
2. Find the two middle terms in the expansion of
y
+
Answer: There are 12 terms in the expansion, so the two middle terms are the
6th (corresponding to k = 5) and the 7th (corresponding to k = 6) terms.

✓ ◆ ✓ ✓32 ◆
11 . 1/ Σ11—5 2 14784x2
x = 462x2
◆5
5 3 y5 = y5

✓ ◆ ✓
11 Σ ✓64 ◆ 29568x5/3
x1/ 11—6 2 = 462x5/3
.3 ◆6 =
y6 y6
6
y
◆10

x3 3
3. Find
of the constant term in the expansion
+ 2 .
2 x
Answer: The general term is
✓ ◆✓ 3 ◆10—k ✓ ◆k ✓ ◆✓ 30—3k ◆✓ k ◆
10 x 3 10 x 3
k = k
2 x2 210—k x2k


10 3k 30—5k
= x
k 210—k

The constant term contains x0, which means 30 — 5k = 0, or k = 6.




10 36 0 76545
x =
4
6 2 8

?2.4.4. Approximation and Combination Identities


We continue applying the Binomial Theorem.
?Example 2.4.8. (1) Approximate (0.8)8 by using the first three terms in the expansion
of (1 — 0.2)8. Compare your answer with the calculator value.

(2) Use 5 terms in the binomial expansion to approximate (0.8)8. Is there an


improvement in the approximation?
Solution
. (0.8)8 = (1 — 0.2)8 ✓
= 8 8
(1)8—k(—0.2)k (—0.2)k
X ◆
=
k= k
0 ✓
8
X8

k
k=
0
2
X ✓8 (—0.2)k = ✓8◆ ✓8 (—0.2) ✓
8 (—0.2)2
(1)
◆ ◆ + ◆

k= +
k 1 2
0 0
= 1 — 1.6+ 1.12 = 0.52
The calculator value is 0.16777216, so the error is 0.35222784.
X4
✓ ✓ ◆ ✓ ✓
(2) 8 (—0.2)k = 8 8 (—0.2) 8 (—0.2)2
◆ ◆ + ◆
+
k= k 1 2

0 0
✓ ◆ ✓ ◆
8 8
+ (—0.2)3 + (—0.2)4
3 4
= 0.52 — 0.448 + 0.112 = 0.184
The error is 0.01622784, which is an improvement on the previous estimate.
2
Example 2.4.9. Use the Binomial Theorem to prove that, for any positive in- teger
n, X
n
✓ ◆
n = 2n.
k=0
k

Solution. Set a = b = 1 in the expansion of (a + b)n. Then


n k=0 ✓ ◆ n k =
2n = (1 + 1)n = X n (1)n

k k
(1)
X ✓ ◆
n
.
k=0 k
Example 2.4.10. Use the Binomial Theorem to prove that
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
+ + + ·· · +
0 2 4 100
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
= + + + ·· · +
1 3 5 99

Solution. Let a = 1 and b = —1 in the expansion of (a + b)100. Then


1 + (—1)⇤10 X100 (1)100—k(—1)k.
✓ ◆
0 100
=
k
k=0
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
0= + (—1) + (—1)2 + (—1)3
0 1 2 3
✓ ◆ ✓ ◆
100 100
+ ·· · + (—1) +
99
(—1)100
99 100
If k is even, then (—1)k = 1. If k is odd, then (—1)k = —1. Hence, we have
0
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
= — + —
0 1 2 3
✓ ◆ ✓ ◆
100 100
+ ·· · — +
99 100

Therefore, after transposing the negative terms to other side of the equation,
we obtain
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
+ + + ·· · +
0 2 4 100
✓ ◆ ✓ ◆ ✓ ◆ ✓ ◆
100 100 100 100
= + + + ·· · + 2
1 3 5 99

Seatwork/Homework 2.4.4
?1. Approximate (1.9)10 using the first three terms in the expansion of
(2 — 0.1)10, and find its error compared to the calculator value.
Answer:

(1.9)10 = (2 — 0.1)10 ⇡
X ✓10
210—k(—0.1)k

2
k= k
0
= 210 — 10 · 29 · 0.1+ 45 · 28 · 0.12
= 627.2

Calculator value = 613.1066258


Error from the calculator value = 14.09337422
2. Prove that, for any positive integer n,
X n ✓ ◆
k=0n 3k = 4n. k
k=0
k X
Xn ✓n◆ n
n—k k
Answer: 4n = (1 + 3)n 1
= 3
= 3k
k=0


n

k
Exercises 2.4
1. Use the Binomial Theorem to expand each expression.
(a) (x — 2)5 Answer: x5 — 10x4 + 40x3 — 80x2 + 80x — 32
1
(b) ✓x + ◆7
y
7x6 21x5 35x4 35x3 21x2 7x 1
Answer: x +
7
+ 2 +
y y + 3 + 4 + 5 + 7
✓ ◆ y y y y6 y
4 ✓ ✓
1 377
(c) 1 Answer: 81 — 3(27) 1◆ + 1◆ — =
3— 8
2 3(9) 8
2 4

2. Without expanding completely, compute the indicated term(s) in the expan-


sion of the given expression.

x3 + ◆
15 , first 3 terms 105x37
Answer: x45 + 15x +
41
(a) 1
2x 4
2
(b) (4 — 3x)6, last 3 terms Answer: 19440x4 — 5832x5 + 729x6

12 3247695
(c) ✓ x 3 , 9th term Answer: x4
2 256
✓ ◆
+
p
1 53130x10
(d) , 6th term Answer:
25 —
x— y5
(e) ✓ y
◆18 12155p9
1 p +1
, middle term Answer:
2
✓ ◆ 128q9
4928
(f) 2 a112 , two middle terms Answer:
9856 4
a 7
+ 81 + 243 a
a 3
.p Σ9
(g) y+x , term involving y3 Answer: 84x3y3

1
366080
(h) ✓13 2x 6 , constant term Answer:
x 729

(i) (xy — 2y—2)21, term that does not contain y Answer: —14883840x14
✓p ◆18
(j) x y , term in which the exponents of x and y are equal
y2 x
Answer: 43758
x 6y6
?3. Approximate (1.1)10 by using the first 4 terms in the expansion of
(1 + 0.1)10. Compare your answer with the calculator result.
Answer: 2.57, with an error of 0.0237424601 from the calculator value of
2.59374246

4. Use the Binomial Theorem to prove that


X n ✓ ◆
n 2k = 3n.
k=0
k

Hint: Expand (1 + 2)n.


5. Use the Binomial Theorem to prove that
6. Hint: Expand (1 — 2)50

You might also like